FIGURE 1 in Phylactolaemate bryozoans at the Zoological Survey of India and a taxonomic key to Indian Phylactolaemata - Wood, Timothy S. (Zenodo, 2022)
FIGURE 1. Fredericella statoblast valves with pitted exterior. (a) Fredericella indica statoblast valve showing a smooth surface at the ends, from Annandale's type specimen, ZSI 3479, valve has curled upon drying; (b) Fredericella borealis showing pitted surface at the ends, from Magerøya Island, Norway; (c) Fredericella indica, lateral view showing smooth region near the suture, from NHMUK 1914.10.2.1, Colombo, Sri Lanka; (d) Enlargement of previous photo; (e) Enlarged view of suture area of F. borealis from Illinois, USA, showing reticulation extending to the suture. Scale bars for a–c = 100 µm, scale bars for d–e = 20 µm. Published as part of Wood, Timothy S., 2022, Phylactolaemate bryozoans at the Zoological Survey of India and a taxonomic key to Indian Phylactolaemata, pp. 401-435 in Zootaxa 5200 (2) on page 403, DOI:10.11646/zootaxa.5200.5.1, http://zenodo.org/record/7270877